Coupling electrooxidation and UV for the treatment, and mineralization of amoxicillin and ibuprofen from aqueous solution: RSM parametric optimization and toxicity assessment - Solomon Ali Yimam; Shimelis Kebede Kassahun; Joon Wun Kang (Results in Engineering)
The study utilized Ti/IrO2 electrodes for electro-oxidation of synthetic wastewater containing amoxicillin and Ibuprofen, with the process optimized using response surface methodology (RSM) within a batch reactor setup. The individual and interactive effects of pH (3 to 9), current density (10-45 mA/cm2), and the initial concentrations of (276-300 µg/L) on COD removal efficiency of the two chemicalsof the two chemicals. The optimal conditions were determined to be pH 3, current density 45 mA/cm2, and initial concentrations of 276 µg/L, resulting in COD removal efficiencies of 79.5% and 95%, for AMOX and IBU respectively. The combination of EO with UV increased TOC removal efficiency for IBU, enhancing mineralization. IBU degraded faster than AMOX, possibly due to its chemical structure's sensitivity to UV photolysis, unlike AMOX. This difference may be due to the extended electrolysis time. For AMOX, the total organic carbon (TOC) measured at 10 minutes was 4.16 ppm, which increased to 6.81 ppm after 30 minutes of treatment. This is primarily because the formation of intermediate products can lead to an increase in the TOC. For IBU, the TOC values at 10 and 30 minutes of treatment were noted to decline from 6.07 ppm to 4.86 ppm, respectively. The study identified intermediate products of AMOX and IBU, proposing a feasible degradation pathway through anodic oxidation using Ti/IrO2 electrodes. The study also conducted toxicity tests on E. coli treated wastewater, revealing that electrolysis alone led to the formation of toxic intermediates that inhibited growth. The maximum Intermediate Removal (IR) achieved was 31% for AMX and 20 % for IBU, exceeding the safety threshold.